PENATALAKSAAN VULVA HYGINE IBU PASCA SALIN MASA PANDEMI - Acholder Tahi Perdoman; Risqi Utami; Fitri Ramadhaniati (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2022)
One of the causes of death in addition to bleeding, pre-eclampsia and complications during the puerperium is infection. The so-called infection during the puerperium is an injury in the birth canal that can cause infection. Injury to the birth canal can occur due to an error during delivery, but it can also occur due to laceration or episiotomy. Episiotomy is performed because it prevents tearing of the perineum, and reduces the strain on the muscles supporting the bladder or ectum that are too strong and prolonged, reducing the length of the second stage. The purpose of this study was to determine the good management of vulvar hygiene and prevention of infection in the birth canal. This research uses a qualitative approach or also called library research. By using the research method of literature or literature study. Results Vulva hygiene is an action to maintain the cleanliness of the external female organs (vulva) which is carried out to maintain health and prevent infection. Conclusion Efforts to prevent infection risk are carried out by providing vulvar hygiene interventions for the perceived perineal wound healing process and recommending patients to perform personal hygiene to keep it clean. Suggestions are for further research on this topic to observe post partum mothers